Channel estimation method for massive MIMO system in Rice channel - Xueli WANG; Haiquan WANG; Xiao LI; Dakuan YANG (Dianxin kexue)
The high-speed mobile transportations,such as high-speed rails,pilot-less airplanes,are mostly in the open areas.Due to the existence of line of sight (LOS) propagations,the Rayleigh fading model can not describe the channels very well in these environments.The Rice fading channel model is constituted of a LOS component and a multiple-path component,which can characterize the channels more accurately.Based on the Rice model,the improved channel estimation methods and corresponding decoding methods were proposed based on the superimposed training sequences for massive multiple input multiple output (MIMO) system.The improved channel estimation methods were divided into two cases:the LOS component was known to the receiver and the other was unknown.The numerical simulation results show that the superiority of the proposed methods.